2010
DOI: 10.4028/www.scientific.net/msf.654-656.412
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Spark-Plasma Sintering: Applications to Net-Shaping of High Strength Temperature Resistant Components

Abstract: Spark-plasma sintering (SPS) is an emerging powder consolidating technique which provides significant advantages to the processing of high temperature materials with poor deformability into configurations previously unattainable. Net-shaping capabilities of spark-plasma sintering are analyzed both theoretically and experimentally. Modeling and experimentation are conducted for cylindrical, prismatic, and complex powder specimen shapes. The impact of the “shape factor” on the non-uniformity of temperature, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…In our earlier work, COMSOL ™ finite element package has been utilized in the above‐mentioned way, thereby enabling the first three‐dimensional fully‐coupled, parallel (same time iteration step) thermo‐electro‐mechanical analysis of the material processing under SPS conditions. In the present article, we describe this approach in detail, applying it for the investigation of SPS scalability potential.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work, COMSOL ™ finite element package has been utilized in the above‐mentioned way, thereby enabling the first three‐dimensional fully‐coupled, parallel (same time iteration step) thermo‐electro‐mechanical analysis of the material processing under SPS conditions. In the present article, we describe this approach in detail, applying it for the investigation of SPS scalability potential.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation, however, is not specific of SPS, but is shared by other techniques involving uniaxial pressing, including hot-pressing. Few successful attempts of producing complex shapes have been presented in the open literature [63][64][65][66], but the topic did not receive large attention. Some patents have been focusing on the possibility of extending the HIP approach to SPS using a gas or a powder as a pressure transfer medium, but the example of applications is still extremely limited [2,3].…”
Section: Industrial Relevancementioning
confidence: 99%
“…Localized electrical current at particle contacts can also contribute to mass transport through electromigration effects which would alter local densification kinetics [11]. This dramatic variation in properties can have a profound effect on the local temperature history and resulting final properties/performance of the part [2,3,12].…”
Section: Introductionmentioning
confidence: 98%
“…Prior modeling efforts to understand thermal-electric gradients during FAST processing include analytical [13], finite difference method [14,15], and finite element modeling (FEM) [1][2][3][4][5]12]. These works generally focus on calculating the temperature and electrical distribution within the system and have shown that the conductivity of the compact plays a large role.…”
Section: Introductionmentioning
confidence: 99%